Simple approach to defining training intensity in endurance runners - Foster, C.; Barroso, R.; Bok, D.; Boullosa, D.; Casado, A.; Cortis, C.; de Knoning, J. J.; Fusco, A.; Haugen, T. (International Journal of Sports Physiology and Performance, 2022)
Training intensity distribution is important to training program design. The zones 1 to 2 boundary can be defined by the Talk Test and the rating of perceived exertion. The zones 2 to 3 boundary can be defined by respiratory gas exchange, maximal lactate steady state, or, more simply, by critical speed (CS). The upper boundary of zone 3 is potential defined by the velocity at maximum oxygen uptake (vVO2max), although no clear strategy has emerged to categorize this intensity. This is not normally definable outside the laboratory.